2021
DOI: 10.1177/20458940211061284
|View full text |Cite
|
Sign up to set email alerts
|

Vascular remodeling of the small pulmonary arteries and measures of vascular pruning on computed tomography

Abstract: Pulmonary hypertension is characterized histologically by intimal and medial thickening in the small pulmonary arteries, eventually resulting in vascular “pruning.” Computed tomography (CT)-based quantification of pruning is associated with clinical measures of pulmonary hypertension, but it is not established whether CT-based pruning correlates with histologic arterial remodeling. Our sample consisted of 138 patients who underwent resection for early-stage lung adenocarcinoma. From histologic sections, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…130 Importantly, the assessment of pruning using this analytic approach in noncontrast CT scans was validated by analyzing preoperative CT scans in relation to the histomorphometric assessment of small arterial remodeling in the lung tissues of patients who underwent lung resection for early-stage adenocarcinoma. 131 The loss of distal small pulmonary arteries using this method has now been shown to segregate individuals with PAH and exercise PH from unaffected controls, with an expected dilatation of large pulmonary arteries in PAH 118 and to predict mortality in the Framingham Cohort. 127 Additionally, changes to intraparenchymal vascular volumes have been described using longitudinal imaging in response to interventions, 132,133 including the acute vasodilator response to inhaled nitric oxide (NO) 134 (Figure 3).…”
Section: Imagingmentioning
confidence: 99%
“…130 Importantly, the assessment of pruning using this analytic approach in noncontrast CT scans was validated by analyzing preoperative CT scans in relation to the histomorphometric assessment of small arterial remodeling in the lung tissues of patients who underwent lung resection for early-stage adenocarcinoma. 131 The loss of distal small pulmonary arteries using this method has now been shown to segregate individuals with PAH and exercise PH from unaffected controls, with an expected dilatation of large pulmonary arteries in PAH 118 and to predict mortality in the Framingham Cohort. 127 Additionally, changes to intraparenchymal vascular volumes have been described using longitudinal imaging in response to interventions, 132,133 including the acute vasodilator response to inhaled nitric oxide (NO) 134 (Figure 3).…”
Section: Imagingmentioning
confidence: 99%
“…The main histologic changes are: intimal hyperplasia through proliferation of smooth muscle cells [ 18 , 21 , 22 ], possibly by dedifferentiation and migration from the media to the intima [ 23 ]; medial thickening [ 24 , 25 ]; and the deposition of elastic and collagen fibers; all this produces thickening of the arterial wall and increased pulmonary vascular resistance [ 26 ]. The progressive luminal narrowing and loss of smaller distal vessels results in the ’pruning’ described in CT scan and angiography [ 27 , 28 ], and the loss of distal arterial vasculature is related to right ventricle (RV) enlargement [ 27 ].…”
Section: Pathophysiologymentioning
confidence: 99%
“…Although asthma is recognized as an inflammatory airway disease, other lung compartments such as the parenchyma and pulmonary vasculature may be modified directly or indirectly, by inflammation. [1][2][3] For example, evidence from cross-sectional and longitudinal studies in severe asthma suggested pulmonary vascular differences in the small vessel volume fraction. 4,5 Reversal of these abnormalities was reported in asthma patients following biologic therapy, as evidenced by a redistribution of blood volume from larger to smaller vessels.…”
Section: Introductionmentioning
confidence: 99%
“…5 It is possible that some of these abnormalities stem from inflammation and pulmonary vascular remodeling. 2,3 Hyperpolarized 129 Xe MRI and MR spectroscopy (MRS) provide a way to quantify the transfer of gas from the airways through the alveolar membrane and its binding to hemoglobin in the red blood cells (RBC) of the pulmonary microvasculature. In these studies, the ratio of 129 Xe binding to the RBC to 129 Xe which has participated in transmembrane diffusion into the alveolar membrane, (RBC:membrane) is utilized as a surrogate of oxygen gas-transfer to the blood.…”
Section: Introductionmentioning
confidence: 99%